1995
DOI: 10.1093/oxfordjournals.aje.a117705
|View full text |Cite
|
Sign up to set email alerts
|

Associations of δ-Aminolevulinic Acid Dehydratase Genotype with Plant, Exposure Duration, and Blood Lead and Zinc Protoporphyrin Levels in Korean Lead Workers

Abstract: Previous studies have suggested that polymorphisms in delta-aminolevulinic acid dehydratase (ALAD), a heme synthetic enzyme, may be associated with differences in blood lead levels, perhaps due to differential binding of lead in erythrocytes. The authors examined associations of ALAD genotype with blood lead and zinc protoporphyrin (ZPP) levels, exposure duration, sex, and plant in 308 currently exposed lead workers in three lead storage battery manufacturing plants in the Republic of Korea in 1993. The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
79
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 0 publications
15
79
1
1
Order By: Relevance
“…In is important to note that the length of exposure to lead, working hours and poor nutritional status may have contributed to these results in subjects with high BLL. Our results indicate that ALAD 1-2/22 variants may not play a substantial role in modulating BLL at higher exposure levels (Schwartz et al, 1995).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In is important to note that the length of exposure to lead, working hours and poor nutritional status may have contributed to these results in subjects with high BLL. Our results indicate that ALAD 1-2/22 variants may not play a substantial role in modulating BLL at higher exposure levels (Schwartz et al, 1995).…”
Section: Discussionmentioning
confidence: 62%
“…At the molecular level, lead displaces a zinc ion at the metal binding site (not the active site) producing inhibition through a change in the enzyme's quaternary structure. This inhibition of ALAD results in the buildup of aminolevulinic acid, detectable in the plasma and urine at BLL less than 10 µg/dl (Schwartz et al, 1995). Thus, ALAD enzyme plays a major role in response to metal poisoning caused by lead, which strongly inhibits ALAD stoichiometrically (Wetmur et al, 1991a;Wetmur et al, 1991b;Schwartz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most human research discusses people with an occupational exposure to lead. SCHWARTZ et al (1995) showed that ALAD2 is more frequent among workers exposed for over 6 years compared to those exposed for less than six years. This may suggest that ALAD2 is favourable in coping with lead intoxication.…”
Section: Discussionmentioning
confidence: 99%